Antibiotic resistance in urban green spaces mirrors the pattern of industrial distribution. (November 2019) - Yan, Zhen-Zhen; Chen, Qing-Lin; Zhang, Yu-Jing; He, Ji-Zheng; Hu, Hang-Wei
Abstract: Urban green spaces are closely related to the activities and health of urban residents. Turf grass and soil are two major interfaces between the environmental and human microbiome, which represent potential pathways for the spread of antibiotic resistance genes (ARGs) from environmental to human microbiome through skin-surface contact. However, the information regarding the prevalence of ARGs in urban green spaces and drivers in shaping their distribution patterns remain unclear. Here, we profiled a wide spectrum of ARGs in grass phyllosphere and soils from 40 urban parks across Greater Melbourne, Australia, using high throughput quantitative PCR. A total of 217 and 218 unique ARGs and MGEs were detected in grass phyllosphere and soils, respectively, conferring resistance to almost all major classes of antibiotics commonly used in human and animals. The plant microbiome contained a core resistome, which occupied >84% of the total abundance of ARGs. In contrast, no core resistome was identified in the soil microbiome. The difference between plant and soil resistome composition was attributed to the difference in bacterial community structure and intensity of environmental and anthropogenic influence. Most importantly, the abundance of ARGs in urban green spaces was significantly positively related to industrial factors including total number of business, number of manufacturing, and number of electricity, gas, water and waste services in the region. Structural equation models further revealed that industrial distribution was a major factor shaping the ARG profiles in urban green spaces after accounting for multiple drivers. These findings have important implications for mitigation of the potential risks posed by ARGs to urban residents. Graphical abstract: Unlabelled Image Highlights: Urban green spaces under no point source pollution are potential antibiotic resistance reservoir. A core resistome was identified among the grass phyllosphere samples. Industrial distribution is a major driver shaping the resistome in urban green spaces.